Peran Unit Usaha Business Center dalam Menumbuhkan Jiwa Berwirausaha di Lingkungan Sekolah Menengah Kejuruan Negeri 9 Semarang - Rr. Hawik Ervina Indiworo; Efriyani Sumastuti; Ayu Putri Mei (Universitas Muria Kudus, 2019)
This research is a qualitative descriptive study. The sources of information in this study are Vice Principals of Facilities and Infrastructure, Business Center Management, entrepreneurship teachers, and students involved in Business Center in SMK Negeri 9 Semarang. Data were collected through interviews, observation and documentation. Validity of data is measured by data triangulation. Data were analyzed qualitatively by using interactive models from Miles and Huberman through data collection, data reduction, data presentation, and conclusions.The results show that Business Center is a potential training place to develop entrepreneurial character where students can have direct practice through it. Management of Business Center in developing entrepreneurial character by using management function that includes planning, implementation and evaluation. Business Center activities can be well directed to achieve so that students may have entrepreneur character which